2017
DOI: 10.1007/s00125-017-4481-2
|View full text |Cite
|
Sign up to set email alerts
|

Maternal obesity as a risk factor for early childhood type 1 diabetes: a nationwide, prospective, population-based case–control study

Abstract: Aims/hypothesis Genetic and environmental factors are believed to cause type 1 diabetes. The aim of this study was to investigate the influence of maternal BMI and gestational weight gain on the subsequent risk of childhood type 1 diabetes. Methods Children in the Swedish National Quality Register for Diabetes in Children were matched with control children from the Swedish Medical Birth Register. Children were included whose mothers had data available on BMI in early pregnancy and gestational weight gain, givi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
4
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 31 publications
1
36
4
1
Order By: Relevance
“…A small number of articles (n = 7) were also excluded for various reasons, including studies that were restricted to the enrolment of participants with genetic susceptibility to type 1 diabetes (human leukocyte antigen [HLA]), studies in which the outcome was islet autoimmunity rather than T1DM, a study that only reported the risk of DM, a study in which the onset of T1DM was not reported, or one study that had overlap of the patient population with another included study . Finally, 21 articles were eligible for the final inclusion in the present meta‐analysis. Of these, 12 were case‐control studies, eight were cohort studies, and one was a cross sectional study .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…A small number of articles (n = 7) were also excluded for various reasons, including studies that were restricted to the enrolment of participants with genetic susceptibility to type 1 diabetes (human leukocyte antigen [HLA]), studies in which the outcome was islet autoimmunity rather than T1DM, a study that only reported the risk of DM, a study in which the onset of T1DM was not reported, or one study that had overlap of the patient population with another included study . Finally, 21 articles were eligible for the final inclusion in the present meta‐analysis. Of these, 12 were case‐control studies, eight were cohort studies, and one was a cross sectional study .…”
Section: Resultsmentioning
confidence: 99%
“…Finally, 21 articles were eligible for the final inclusion in the present meta‐analysis. Of these, 12 were case‐control studies, eight were cohort studies, and one was a cross sectional study . The characteristics of the included studies are summarized in Tables S1 ‐ S3.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations